Linguistic Approach in The Study of Literature (Eurasian Research Bulletin, 2022)
Research on the language of literature has a long tradition under the rubric of philology. This unity of concerns has lapsed as linguistics has become independent and linguistic training for literary scholars has been virtually eliminated. Still, the linguistic revolution of the last four decades has produced substantial work by linguists in prose style, narrative, metrics, poetic syntax, and metaphor.